Frequencies of the Transferrin Alleles and Genotypes in Crossbred Cattle and their Effect on Growth Traits - Mukherjee, T. K.; Yap, T. N. (1979)
Records on birth weight, body 'weight and body measurement traits were obtained from a total of 149 crossbred animals (Zebu X Temperate) from the lnstitut Haiwan Kluang, From the blood samples collected from these animals, 14.5 of them were analysed for the presence of serum transferrin genotypes. Frequency of the TID gene was found to be highest in both the half bred and quarter-bred Zebus, Frequency of lyA and lyE was found to be lower and higher respectively in half-bred Zebus and the quarter-bred Zebus. In general, there were no significant variations (P < a.OS) between the effects of different transferrin genotypes observed (TfAA, Tf:1D, 7y/n, l/DD alld 1/D1\) on any of the body weight or body conformation trait,